Peran Human Capital, Corporate Value dan Good Corporate Governance melalui Kinerja Karyawan terhadap Kinerja Perusahaan di PTPN VII Lampung - Husen Sutisna; Aida Vitayala S. Hubeis; Muhammad Syamsun (MANAJEMEN IKM: Jurnal Manajemen Pengembangan Industri Kecil Menengah, 2014)
Changes in business environment lead various companies to continue to strive to improve their business strategies in order to survive and have a competitive advantage. The peak changes occurred with the coming of business era in the era of information and science. In this era, business strategies that are considered suitable, among others, the application of human resource development system based on human capital and company management based on corporate values and good corporate governance (GCG). PTPN VII as state-owned enterprise in agribusiness has tried to implement the system. This study aimed to examine the relationship between human capital, corporate values ​​and GCG and their relation to the performances of the employees and the company. The population of this research as many as 400 people consisted of the employees of PTPN VII head office, but the number of the samples set  was 120 respondents. The sampling technique used was non-probability sampling with quota sampling technique. The methods of processing and analyzing the data was structural equation modeling analysis-partial least squares (SEM-PLS),  and the data processing used software smartPLS. The results indicated that the implementation of human capital by the company contributed positively to the increase of the employee performance. The implementation and internalization of corporate values ​​to the employees positively contributed to the improvement of the employee performance. The increased employee performance  played a positive role in improving the company performance. The implementation of corporate governance principles could improve the performance of the company, but did not play a great role in improving employee performance